Self-Regulation Failure? The Influence Mechanism of Leader Reward Omission on Employee Deviant Behavior - Wang, Tian; Cao, Zhoutao; Zhong, Xi; Chen, Chunhua (Frontiers in Psychology, 2021)
In existing research, leader contingent reinforcement behavior is regarded as one of the essential elements of being a “good” leader. However, the question of what happens when this behavior is absent has received little attention in empirical research. To uncover the underlying mechanisms, this study explored the effects of leader reward omission on employees' deviant behavior via moral disengagement based on the data of 230 employees collected across three-time points. The results indicated that the positive indirect effects of leader reward omission on employees' deviant behavior were mediated by moral disengagement. Machiavellianism was also found to strengthen the extent to which employees experienced moral disengagement, and these effects carried through to affect employees' deviant behavior.